Methotrexate associated with a lipid core nanoparticle prevented the dilation and dissection of the aortic arch in mice with Marfan syndrome. (25th November 2020) - Guido, M.C; Lopes, N.M; Albuquerque, C.I; Tavares, E.R; Jensen, L; Pereira, L.V; Kalil-Filho, R; Laurindo, F.R.M; Maranhao, R.C
Abstract: Introduction: Mutations in the fibrillin-1 gene result in dilation, dissection and rupture of the aorta, the main cause of mortality in patients with Marfan syndrome (MFS). Inflammation is associated with greater susceptibility to dissection and rupture of the aorta. Previously, we showed that methotrexate (MTX) carried in lipid core nanoparticles (LDE) had powerful anti-inflammatory and anti-proliferative effects on rheumatoid arthritis and atherosclerotic lesions induced in rabbits and improved myocardial infarction morphological and functional aspects in rats with ligation of left coronary artery. When MTX is associated to LDE, the uptake of the drug by the cells is increased several-fold, which conceivably endows MTX with enhanced action mechanisms and the drug toxicity is diminished. Purpose: To investigate whether treatment with LDE-MTX can prevent the development of aortic arch lesions in a murine model of MFS. Methods: mgΔloxPneo MFS murine model and wild-type mice were allocated in 3 groups of treatment: LDE only; MTX in commercial formulation; LDE-MTX. The treatment occurred weekly at a dose of 1mg/kg ip, between the 3rd and 6th month of life, period in which both dilation and dissection of the aortic arch are observed. After 12 weeks, the animals were submitted to echocardiography, morphometry and protein expression of the aortic arch. Results: Compared to LDE and MTX groups, LDE-MTX treatment showed smaller lumen area of ascending and descending aorta and aortic arch segments in MFS mice. LDE-MTX also decreased the collagen volume fraction and the amount of aortic dissections, but did not affect the thickness of the vessel wall and the number of elastic fiber ruptures. The protein expression of the inflammatory markers CD68 (macrophages), CD3 (lymphocytes) and tumor necrosis factor alpha, of the apoptotic marker caspase 3 and of type 1 collagen were lower in MFS LDE-MTX group when compared to MFS mice treated with LDE and MTX. Moreover, treatment with LDE-MTX reduced TGF-β, ERK and the SMAD3 protein expression. Of note, CD68 and CD3 protein expression was positively correlated with the lumen area of the aortic arch (r2=0.36; p<0.001), indicating the importance of inflammation for the aortic dilation. The increase in bioavailability of intracellular adenosine in MFS animals treated with LDE-MTX was suggested by the higher expression of A2a adenosine receptor and the lower expression of adenosine deaminase in the aortic arch. Conclusion: Possibly by increasing the bioavailability of intracellular adenosine, LDE-MTX treatment had the ability to reduce the processes of inflammation, apoptosis and fibrosis that are consequent to fibrillin-1 mutation. By these means, LDE-MTX may conceivably prevent the development of the dilation and dissection in the aortic arch, the hallmarks of MFS, in this animal model. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): FAPESP (Fundação de Amparo à Pesquisa do Estado de São Paulo)